Konsep Pembelajaran Guru Yang Bermutu - Mohamad Mustafid Hamdi (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2019)
Through learning there will be a process of developing religious morals, activities, and creativity of students through various interactions and learning experiences. In principle, learning is not the same as teaching. Learning emphasizes the activities of students, while teaching emphasizes the activities of educators.Quality is a description that explains the good and bad results achieved by students in the educational process carried out, while another understanding explains that quality is a measure of good and bad, quality, level, grade, or degree and intelligence, intelligence and so on.Learning is the process of student interaction with educators and learning resources in a learning environment. Simple learning can be interpreted as an attempt to influence emotional, intellectual, and spiritual so that they want to learn with their own will.Teacher quality is the level of quality of an educator in providing education and learning to students in order to fulfill their authority and responsibilities both at school and outside school